2007
DOI: 10.1080/13550280701620747
|View full text |Cite
|
Sign up to set email alerts
|

Associations of cigarette smoking with viral immune and cognitive function in human immunodeficiency virus–seropositive women

Abstract: Cigarette smoking alters the immune system and may improve cognitive deficits in neuropsychiatric disorders. Smoking prevalence is high in human immunodeficiency virus (HIV)-infected patients; however, its effect on HIV-associated cognitive impairment remains unknown in the era of antiretroviral treatment. The authors examined associations of smoking with viral immune profile and cognitive function in a cohort of HIV-seropositive women. This observational cross-sectional study included 56 women (36 HIV-seropos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 51 publications
5
49
0
2
Order By: Relevance
“…These effects could potentially result in nicotine inducing an overall enhancement of inflammatory responses, which could exacerbate the nervous system damage that can occur in HIV-infected individuals. Such effects would be consistent with studies that show that smoking has deleterious effects on cognitive functioning among HIV-infected individuals (Chang et al 2017; Harrison et al 2017; Wojna et al 2007), although the specificity of such effects has been questioned (Bryant et al 2013). …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These effects could potentially result in nicotine inducing an overall enhancement of inflammatory responses, which could exacerbate the nervous system damage that can occur in HIV-infected individuals. Such effects would be consistent with studies that show that smoking has deleterious effects on cognitive functioning among HIV-infected individuals (Chang et al 2017; Harrison et al 2017; Wojna et al 2007), although the specificity of such effects has been questioned (Bryant et al 2013). …”
Section: Discussionsupporting
confidence: 85%
“…HIV-infected smokers also have a higher mortality than infected nonsmokers and HIV-negative individuals (Helleberg et al 2013), suggesting likely direct effects from smoking and interactions between smoking and HIV-1 infection on mortality. Also, although data may be conflicting as to whether cigarette smoking can increase progression to AIDS (Galai et al 1997; Nieman et al 1993), smoking has been associated with an increased HIV plasma viral load (Wojna et al 2007), and an increased risk of developing neurocognitive impairment (Harrison et al 2017; Wojna et al 2007). Approximately 40% of HIV-positive individuals are cigarette smokers (Lifson and Lando 2012), which is more than twice the prevalence of smoking among adults in the general population (Jamal et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have addressed the effects of smoking on cognitive function and neurological disorders in the HIV-1-infected individuals with controversial findings [36]. Of relevance, it has been reported that chronic nicotine exposure can lead to the disruption of the blood–brain barrier (BBB) integrity, which may enhance the exposure to HIV-1-infected monocytes, tobacco constituents and antiretroviral drugs [37].…”
Section: Role Of Smoking On Hiv-1 Pathogenesismentioning
confidence: 99%
“…The exposure of these agents to CNS may exacerbate neuroAIDS and neurodegenerative diseases [37]. Another report from an observational cross-sectional study conducted in 56 women (36 HIV-1-infected and 20 non-HIV-1- infected) suggests that there is no correlation between smoking and cognitive dysfunction [36] in the HIV-1-infected population. Collectively, the available evidence suggests that there is an increase in smoking-mediated HIV-1 pathogenesis among individuals with HIV-1/AIDS and patients may benefit from the development of novel therapeutic agents and/or drug dose adjustments that can be used to treat HIV-1-infected smokers effectively.…”
Section: Role Of Smoking On Hiv-1 Pathogenesismentioning
confidence: 99%
“…Since nicotine exposure has been shown to disrupt the blood-brain barrier (Manda et al, 2010), HIV-1-infected monocytes/macrophages can infiltrate the brain and infect microglia, astrocytes, and perivascular macrophages (Kedzierska and Crowe, 2002;Montaner et al, 2006). In addition, smoking has been shown to decrease the response to antiretroviral therapy that enhances the risk of viral replication (Feldman et al, 2006;Wojna et al, 2007).…”
Section: Introductionmentioning
confidence: 99%